2011
DOI: 10.4209/aaqr.2011.02.0017
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Source Identification of Particulate Matter at an Urban Site of Navi Mumbai, India

Abstract: Particulate matter samples were collected using a dichotomous sampler at a residential area of Vashi situated in Navi Mumbai, India during the period of 2008. The sampler facilitates the simultaneous collection of atmospheric particulates in coarse and fine size fractions. The filter samples collected were analysed for trace elements using Proton Induced X-ray Emission (PIXE) technique. The particulate matter trends show higher concentration during winter season compared to other seasons. High concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 43 publications
2
28
6
Order By: Relevance
“…The BC source apportionments at all of the locations revealed that New Zealand had highest percentage of black carbon from biomass with values as high as 82% while Mongolia had the lowest percentage of 3.1%. Emissions from diesel vehicles to black carbon concentration were found to be dominant in Mumbai, India with values up to 80% (Kothai et al, 2011). Alternatively, Mongolia has the lowest emission of BC from diesel vehicle as 5.4%.…”
Section: Resultsmentioning
confidence: 99%
“…The BC source apportionments at all of the locations revealed that New Zealand had highest percentage of black carbon from biomass with values as high as 82% while Mongolia had the lowest percentage of 3.1%. Emissions from diesel vehicles to black carbon concentration were found to be dominant in Mumbai, India with values up to 80% (Kothai et al, 2011). Alternatively, Mongolia has the lowest emission of BC from diesel vehicle as 5.4%.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of fog and haze is associated with high aerosol loading from anthropogenic sources as well as formation of secondary aerosols via gas-to-particle conversion under favorable meteorological conditions (Reilly et al, 2001;Husain et al, 2004;Sun et al, 2006;Fang et al, 2011;). Recent studies suggest that a significant fraction of atmospheric particulate matter (PM) in the Indo-Gangetic Plain are comprised of carbonaceous aerosol (~30-35% of the PM) and water-soluble inorganic species (~10-20% of the PM) over IGP and other locations in India Rengarajan et al, 2007;Ram et al, 2010a;Deshmukh et al, 2011;Kothai et al, 2011). During the wintertime, low ambient temperatures (range: ~10-20°C, at times dipping as low as 5°C) and weak winds (< 2 m/s) and boundary layer height (~500-800 m) favour stable atmosphere, leading to poor convective mixing and accumulation of pollutants in the lower atmosphere (Nair et al, 2007;Ram et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…This factor could be attributed to the textile related industries. Since Cu and Cr complexes are mostly used in abundance in the industries of textile, dyes and intermediates, it is suspected that this could be the source of emission for these elements having high loadings in the fifth factor of fine particulates (Kothai et al, 2011). Also about 6% of the industries in the nearby industrial belt comprise dye and textile industries (Srivastava and Som, 2007).…”
Section: Source Identification Of Fine Pm Using Famentioning
confidence: 99%
“…The irradiated samples are then analysed by gamma spectrometry using a High Purity Germanium coaxial P-type detector with 50% relative efficiency and with an energy resolution of 2 keV at 1,332 keV energy. Information regarding elemental analysis using INAA is presented elsewhere in detail (Kothai et al, 2011).…”
Section: Elemental and Bc Characterizationmentioning
confidence: 99%